The Prognostic Value of Immune Factors in the Tumor Microenvironment of Penile Squamous Cell Carcinoma - Ottenhof, Sarah Rosanne; Djajadiningrat, Rosa Sanne; Thygesen, Helene Hoegsbro; Jakobs, Pamela Josephine; Jóźwiak, Katarzyna; Heeren, Anne Marijne; de Jong, Jeroen; Sanders, Joyce; Horenblas, Simon; Jordanova, Ekaterina Straschimirova (Frontiers in Immunology, 2018)
The host’s immune system plays a pivotal role in many tumor types, including squamous cell carcinomas (SCCs). We aim to identify immunological prognosticators for lymph node metastases (LNM) and disease specific survival (DSS) in penile squamous cell carcinoma (SCC). For this retrospective observational cohort study, penile SCC patients (n=213) treated in the Netherlands Cancer Institute, were selected if sufficient formalin-fixed, paraffin-embedded tumor material was available. Analysis included previously described high-risk human papilloma virus (hrHPV)-status, immunohistochemical scores for classical and non-classical human leukocyte antigen (HLA) class I, Programmed Death-Ligand 1 (PD-L1) expression, and novel data on tumor infiltrating macrophages and cytotoxic an regulatory T-cells. Clinicopathological characteristics and extended follow-up was also included. Regression analyses investigated relationships of the immune parameters with LNM and DSS. In the total cohort, diffuse PD-L1 tumor-cell expression, CD163+ macrophage infiltration, non-classical HLA class I upregulation and low stromal CD8+ T-cell infiltration, were all associated with LNM. In the multivariable model, only tumor PD-L1 expression remained a significant predictor for LNM (OR2.8, p=0.05). HrHPV-negativity and diffuse PD-L1 tumor-cell expression were significantly associated with poor DSS and remained so upon correction for clinical parameters (HR9.7, p<0.01 and HR2.8, p=0.03).The only immune factor with different expression in HPV+ and HPV- tumors was PD-L1, with higher PD-L1 expression in the latter (p=0.03). In the HPV- cohort (n=158), LNM were associated with diffuse PD-L1 tumor-cell expression, high intratumoral CD163+ macrophage infiltration and low number of stromal CD8+ T-cells.The first two parameters were also linked to DSS. In the multivariable regression model, diffuse PD-L1 expression remained significantly unfavorable for DSS (HR5.0, p<0.01). These results emphasize the complexity of the tumor-microenvironment in penile cancer and point towards several possible immunotherapy targets. The here described immune factors can aid risk-stratification and should be evaluated in clinical immunotherapy studies to ultimately lead to patient tailored treatment.